Purslane and natural vegetation as bioremediation tools to cope salinity in Satsuma mandarin orchards - Cenk Ceyhun Kılıç; Dilek Anaç; Uygun Aksoy; Süer Anaç (African Journal of Environmental Economics and Management, 2020)
The objective of this study is to compare the Na and Cl removal capacity of natural vegetation (spontaneous flora) and cultivated purslane, as bioremediation techniques to overcome salinity in Satsuma mandarin plantations. An experimental orchard was established on two different rootstocks, (Poncirus trifoliata L.) Raf. and Troyer citrange (Poncirus trifoliata × Citrus sinensis)) and the orchard was irrigated at 2 different salinity levels (0.65 and 5 dSm-1.The ground of the on rows of Satsuma mandarin trees was kept either with its natural flora (vegetation) or with cultivated purslane. Results are statistically examined with respect to the effects and interactions between the tested factors; rootstock, salinity and remediation tools. Biomass yields of the tested alternatives (natural vegetation and purslane) and their Na, Cl, K and Ca concentrations were measured. Also Na and Cl concentrations of mandarin leaves were analyzed to examine the remediation effect. Results showed that yield depressions of the natural vegetation plots were higher compared to purslane and showed a considerable difference according to the rootstock. Sodium removal of purslane and natural vegetation was found to be similar. Chloride uptake was lower in Troyer citrange compared to P. trifoliata. Purslane and/or natural vegetation can equally be recommended as Na removing bioremediation crops. Purslane can also be recommended as a promising Cl remover suitable for orchards on P. trifoliata (L.) Raf. rootstock.